A Study of Psychoactive Medicines and Risk of Falls Among Indonesian Elderly Patients - Fita Rahmawati; Nasikhatul Mustafidah; I Dewa Putu Pramantara; Izyan Abdul Wahab (Indonesian Journal of Pharmacy, 2019)
One of the causes of injury to the elderly is due to falls. Falling can be prevented by identifying and controlling risk factors. One risk factor that can be controlled is the use of fall risk medicines including psychoactive. This study aims to identify the association between the use of psychoactive medicine and its characteristic with the risk of falls among the elderly in Indonesia.  The study utilized a case-control study design for a total number of 414 elderly patients, during October until December 2018. Cases were elderly aged 60 years or above with a high risk of falling assessed using the Morse Fall Scale (MFS≥45). Each case was matched with up to two randomly selected controls of the same age who are classified as low to moderate risk of falling (MFS<45). The use of psychoactive medicines was screened from a history of drug use for the past six months. Psychoactive medicine-fall risk associations were estimated via logistic regression. There were 138 cases and 276 controls. The median age of subjects was 66 years old and 54.83% was a woman. Elderly with a high risk of falling had higher psychoactive medicines use when compare with controls (31.16 % vs 21.38 %, p< 0.05). After adjusting for potential confounders, the use of psychoactive medicines was significantly associated with higher fall risk in elderly patients (OR 1.79 95% CI 1.10-2.90). Only the duration of psychoactive medication use over 90 days was significantly associated with a high risk of falling (AOR 3.65 95% CI 1.46-9.14). In elderly patients, the continued use of psychoactive medicines increased the risk of fall. Prescribers need to weigh risk and benefit from the use of psychoactive medicines in the elderly to prevent future fall.